Peningkatan Penggunaan Social Learning Network Bagi Siswa-Siswi SMP Negeri 2 Syamtalira Aron Kab. Aceh Utara - Juni Ahyar; Ikramuddin Ikramuddin; T. Edyansyah; Rizka Astuti; Maqfiratun Misla (Empowerment: Jurnal Pengabdian Masyarakat, 2023)
Today the development of the internet is increasing rapidly and has penetrated into several fields, including the field of education. Learning media also develops and creates a Social Learning Network. Edmodo is an online learning medium that combines several Learning Management Systems and Social Network features into a Social Learning Network specifically made for educational purposes. To obtain an effective learning process, teachers and students must have innovative and interesting learning media, this is what is experienced by SMP Negeri 2 Syamtalira Aron North Aceh Regency. Teachers of SMP Negeri 2 Syamtalira Aron North Aceh Regency have carried out training on increasing the use of Edmodo learning media, but students still have not used social network-based learning media. This is the background for the service team to provide training on "Increasing the Use of Social Learning Network for Students of SMP Negeri 2 Syamtalira Aron North Aceh Regency ". This activity was held at the Syamtalira Aron 2 Public Middle School Computer Lab using lecture methods and hands-on practice. The participants of this training were 30 people, all of whom were students of SMP 2 Syamtalira Aron North Aceh Regency. The activity lasts for one day with a duration of four hours. Through this activity, it is hoped that the participant's skills and understanding will increase regarding the use of the Edmodo learning social network